Optimizing in-plane strength of honeycomb structures to achieve quasi-isotropic performance - Khalid Alblalaihid; Saad Aldoihi; Safwan Alblihed; Hani Algaan; Sami S. Alsaleh; Basheer A. Alshammari; Ibrahim A. Alshunaifi; Anas Almuqhim; Khalid Khormi; Meshal Abuobaid; Abdulmalik Alshamikh (Materials & Design, 2025)
Honeycomb structures are widely employed in aerospace, automotive, and engineering applications due to their excellent strength-to-weight ratio. However, conventional honeycomb designs—particularly those fabricated via 3D printing—often suffer from pronounced in-plane anisotropy, which limits their mechanical performance under multi-directional loading. This study introduces a modified honeycomb design aimed at achieving quasi-isotropic in-plane behavior. Using fused filament fabrication (FFF) with polyamide 6 (PA6) reinforced with 15 % short carbon fibers, honeycomb structures were fabricated with a [±45°, 90°, 0°]s layer orientation. Experimental tensile tests and finite element analysis (FEA) demonstrated a significant reduction in anisotropy, with elastic modulus variation across 0°, 45°, and 90° directions reduced to under 3 %. In-plane compression tests further validated the design, revealing modulus variation below 2 % and a flatter, more stable stress plateau. This behavior confirms enhanced progressive collapse and improved energy absorption compared to conventional honeycomb structures.